Exprimental Study of Liquid Drop Surface Transformation in Air Within a Group of Successive Deformation Cycles; Chemical and Petroleum Engineering; Vol. 52, iss. 9-10 - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Kuibin P. A. (2017, 2017)
Title screen